Arylamine compound, organic electroluminescent element and electronic device
By developing an aromatic amine compound with carbazolyl and optimized naphthylene position, the problem of insufficient heat resistance and electron barrier properties of organic EL components under high temperature conditions is solved, and an organic EL component with high efficiency, low driving voltage and long life is achieved.
Patent Information
- Application Number
- CN202380059015.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-11
- Publication Date
- 2025-03-21
AI Technical Summary
Existing organic electroluminescent (EL) components have poor heat resistance under high temperature conditions and insufficient electron barrier properties of hole transport materials, resulting in poor luminescence efficiency and component life.
A new aromatic amine compound is developed to enhance the hole injection, transport performance and electron barrier capability of the compound by introducing carbazolyl and optimizing the position of naphthene group, thereby enhancing its film stability and heat resistance.
High efficiency and high power efficiency luminescence is achieved, reducing the luminescence starting voltage and practical driving voltage, and improving the long life and durability of the components.
Smart Images

Figure CN119677719A_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound and a component suitable for an organic electroluminescent component (hereinafter referred to as an organic EL component) as a self-luminous component suitable for various display devices, and in particular, to an aromatic amine compound and an organic EL component using the same.
[0002] [Prior Art]
[0003] Organic EL devices are self-luminous devices that are brighter and more visible than liquid crystal devices. Therefore, research has been actively conducted to achieve clear displays.
[0004] In 1987, CW Tang and others from Eastman Kodak developed a laminated structure component that divided the roles among the materials, thus making organic EL components using organic materials a reality. They laminated a phosphor that can transfer electrons and an organic substance that can transfer holes, and injected charges from both sides into the phosphor layer to make it emit light, thereby obtaining 1000 cd / m at a voltage of less than 10V. 2 The above high brightness (for example, refer to Patent Document 1 and Patent Document 2).
[0005] To date, many improvements have been made for the practical application of organic EL components, and the various functions of the layered structure have been further refined, thereby achieving high efficiency and durability by having an electroluminescent component in which an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode are sequentially arranged on a substrate (for example, refer to non-patent document 1).
[0006] In addition, attempts have been made to utilize triplet excitons in order to further improve the luminous efficiency, and the use of phosphorescent compounds has been studied (for example, see Non-Patent Document 2). In addition, a component utilizing luminescence achieved by thermally activated delayed fluorescence (TADF) has also been developed. In 2011, Adachi et al. of Kyushu University achieved an external quantum efficiency of 5.3% by using a component using a thermally activated delayed fluorescence material (for example, see Non-Patent Document 3).
[0007] The light-emitting layer can also be prepared by doping a fluorescent compound, a phosphorescent compound, or a material emitting delayed fluorescence into a compound having charge transport properties, which is generally referred to as a host material. As described in the above-mentioned non-patent document, the selection of organic materials in an organic EL component has a significant impact on various characteristics of the component, such as efficiency and durability (for example, refer to non-patent document 2).
[0008] In an organic EL component, the charges injected from the two electrodes are recombined in the light-emitting layer to achieve light emission, but it is important to effectively transmit the two charges of holes and electrons to the light-emitting layer, so it is necessary to set it as a component with excellent carrier balance. Therefore, by using a material with the characteristics of improving the hole injection property of supplying holes injected from the anode to the light-emitting layer and improving the electron blocking property of blocking electrons injected from the cathode, the probability of holes and electrons recombination in the light-emitting layer can be increased, and then, by binding the excitons generated in the light-emitting layer, high luminous efficiency can be obtained. For this reason, the role played by the hole transport material is more important, and a hole transport material as follows is required: high hole injectability, large hole mobility, high electron blocking property, and high durability to electrons.
[0009] In addition, regarding the life of the component, the heat resistance or amorphousness of the material is also important. Materials with low heat resistance will also undergo thermal decomposition at lower temperatures due to the heat generated when the component is driven, causing the material to deteriorate. Materials with low amorphousness will also undergo thin film crystallization in a shorter period of time, causing the component to deteriorate. Therefore, the materials used are required to have high heat resistance and good amorphous properties.
[0010] As hole transport materials used in organic EL devices so far, there are N,N'-diphenyl-N,N'-di(α-naphthyl)benzidine (NPD) or various aromatic amine derivatives (for example, see Patent Documents 1 and 2). However, although NPD has good hole transport ability, its glass transition point (Tg), which is an indicator of heat resistance, is as low as 96°C. Under high temperature conditions, it crystallizes, resulting in a decrease in device characteristics (for example, see Non-Patent Document 4).
[0011] In addition, among the aromatic amine derivatives described in the above patent documents, there is a -3 cm 2 / Vs or more excellent mobility compounds (for example, see Patent Documents 1 and 2), but the electron blocking property is insufficient, so part of the electrons leave the light-emitting layer, and it is not expected to improve the luminous efficiency, etc. In order to further achieve high efficiency, a material with higher electron blocking property, more stable thin film and higher heat resistance is required. In addition, although there are reports of aromatic amine derivatives with high durability (for example, see Patent Document 3), they are used as charge transport materials for electronic photography photoreceptors, and there is no precedent for their use as organic EL components.
[0012] In order to solve the above-mentioned problems, a substituted carbazole structure or aromatic amine compound (for example, refer to Patent Document 4 and Patent Document 5) has been proposed as a compound having improved properties such as heat resistance and hole injection property. When these compounds are used in components of hole injection layer or hole transport layer, component life and luminous efficiency are improved, but still insufficient, and further realization of lower driving voltage or higher luminous efficiency and longer component life is required.
[0013] [Previous Technical Literature]
[0014] [Patent Literature]
[0015] (Patent Document 1) U.S. Patent No. 5792557
[0016] (Patent Document 2) U.S. Patent No. 5,639,914
[0017] (Patent Document 3) U.S. Patent No. 7759030
[0018] (Patent Document 4) JP2009076817A1
[0019] (Patent Document 5) JP6674892B2
[0020] (Patent Document 6) European Patent No. 2684932
[0021] (Patent Document 7) KR101888249B1
[0022] (Patent Document 8) KR102259465B1
[0023] (Patent Document 9) KR102078171B1
[0024]
Non-patent literature
[0025] (Non-patent document 1) Notice of the 9th Seminar of the Society of Applied Physics, pp. 55-61 (2001)
[0026] (Non-patent document 2) Notice of the 9th Seminar of the Society of Applied Physics, pp. 23-31 (2001)
[0027] (Non-patent document 3) Appl. Phys. Let., 98, 083302 (2011)
[0028] (Non-patent document 4) Organic EL Symposium 3rd Regular Meeting Notice, pp. 13-14 (2006) [Summary of the invention]
[0029] [Problems that the invention aims to solve]
[0030] The object of the present invention is to provide a material for an organic EL component having the following characteristics: (1) excellent hole injection and transport performance, (2) electron blocking ability, (3) high stability in a thin film state, and (4) excellent durability when developing a high-efficiency and high-durability organic EL component.
[0031] By using the material of the present invention, an organic EL device is provided which has (1) high luminous efficiency and power efficiency, (2) low luminous starting voltage and practical driving voltage, and (3) long life.
[0032] [Technical means to solve the problem]
[0033] In order to achieve the above-mentioned object, the inventors of the present invention focused on the excellent hole injection and transport capabilities of aromatic amine compounds, and the stability and durability of thin films. By introducing carbazole groups to expand the band gap, the introduction of substituted naphthylene groups and the optimization of substitution positions were pursued, thereby dramatically improving the characteristics of the material. For organic EL components, the performance of luminous efficiency and power efficiency is also improved, so that the luminous starting voltage and practical driving voltage can be suppressed, thereby achieving a longer life than before, and completing the present invention.
[0034] (1) That is, the present invention is an aromatic amine compound represented by the following general formula (I).
[0035]
[0036] In the formula, A represents a substituted or unsubstituted aromatic hydrocarbon group, a substituted or unsubstituted aromatic heterocyclic group, or a substituted or unsubstituted condensed polycyclic aromatic group,
[0037] B represents a substituted or unsubstituted carbazolyl group,
[0038] C represents an unsubstituted naphthylene group,
[0039] R represents an unsubstituted aromatic hydrocarbon group, an unsubstituted aromatic heterocyclic group, or an unsubstituted condensed polycyclic aromatic group,
[0040] L1 to L3 represent a single bond, an unsubstituted divalent aromatic hydrocarbon group, an unsubstituted divalent aromatic heterocyclic group, or an unsubstituted divalent condensed polycyclic aromatic group.
[0041] (2) In addition, the present invention is an aromatic amine compound as described in (1) above, wherein C in the general formula (I) represents an unsubstituted 1,2-naphthylene, an unsubstituted 1,3-naphthylene, an unsubstituted 2,4-naphthylene, an unsubstituted 2,5-naphthylene, an unsubstituted 2,6-naphthylene, an unsubstituted 2,7-naphthylene, or an unsubstituted 2,8-naphthylene.
[0042] (3) In addition, the present invention is the aromatic amine compound as described in (2) above, wherein L2 and L3 in the general formula (I) represent an unsubstituted phenylene group or an unsubstituted biphenylene group.
[0043] (4) In addition, the present invention is an aromatic amine compound as described in (3) above, wherein R in the general formula (I) represents an unsubstituted phenyl group, an unsubstituted naphthyl group, an unsubstituted dibenzofuranyl group, an unsubstituted phenanthrenyl group, or an unsubstituted biphenyl group.
[0044] (5) In addition, the present invention is an aromatic amine compound as described in (4) above, wherein B in the general formula (I) represents a substituted or unsubstituted 9-carbazolyl group, a substituted or unsubstituted 2-carbazolyl group, or a substituted or unsubstituted 3-carbazolyl group.
[0045] (6) In addition, the present invention is the aromatic amine compound as described in (5) above, wherein B in the general formula (I) represents an unsubstituted 9-carbazolyl group.
[0046] (7) In addition, the present invention is an organic EL device having a pair of electrodes and at least one organic layer sandwiched between the electrodes, wherein the organic layer comprises the aromatic amine compound described in (1) or (2) above.
[0047] (8) Furthermore, the present invention is the organic EL device as described in (7) above, wherein the organic layer is a hole transport layer.
[0048] (9) Furthermore, the present invention is the organic EL device as described in (7) above, wherein the organic layer is an electron blocking layer.
[0049] (10) Furthermore, the present invention is the organic EL device as described in (7) above, wherein the organic layer is a hole injection layer.
[0050] (11) Furthermore, the present invention is the organic EL device as described in (7) above, wherein the organic layer is a light-emitting layer.
[0051] (12) In addition, the present invention is an electronic device comprising a pair of electrodes and at least one organic layer sandwiched between the electrodes, wherein the organic layer comprises the aromatic amine compound according to (1) or (2) above.
[0052] The "aromatic hydrocarbon group", "aromatic heterocyclic group" or "condensed polycyclic aromatic group" in the "substituted or unsubstituted aromatic hydrocarbon group", "substituted or unsubstituted aromatic heterocyclic group" or "substituted or unsubstituted condensed polycyclic aromatic group" represented by A in the general formula (I) specifically includes phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthryl, indenyl, pyrenyl, peryl, fluoranthenyl, benzo[9,10]phenanthryl, fluorenyl, spirobifluorenyl, pyridyl, pyrimidinyl, triazine, In addition to furanyl, pyrrolyl, thienyl, quinolyl, isoquinolyl, benzofuranyl, benzothienyl, indolyl, carbazolyl, benzoxazolyl, benzothiazolyl, azafluorenyl, diazafluorenyl, azaspirobifluorenyl, diazaspirobifluorenyl, quinoxalinyl, benzimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothienyl, naphthyridinyl, phenanthrolinyl, acridinyl and carbolyl, aryl groups having 6 to 30 carbon atoms or heteroaryl groups having 2 to 20 carbon atoms can be mentioned.
[0053] Specific examples of the "substituent" in the "substituted aromatic hydrocarbon group", "substituted aromatic heterocyclic group" or "substituted condensed polycyclic aromatic group" represented by A in the general formula (I) include a deuterium atom, a cyano group, a nitro group; a halogen atom such as a fluorine atom, a chlorine atom, a bromine atom, an iodine atom; a silyl group such as a trimethylsilyl group and a triphenylsilyl group; a linear or branched alkyl group having 1 to 6 carbon atoms such as a methyl group, an ethyl group and a propyl group; a linear or branched alkoxy group having 1 to 6 carbon atoms such as a methoxy group, an ethoxy group and a propoxy group; an alkenyl group such as a vinyl group and an allyl group; a phenoxy group, a tolyloxy group, etc. Aryloxy; aralkyloxy such as benzyloxy and phenethoxy; aromatic hydrocarbon groups or condensed polycyclic aromatic groups such as phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluorenyl, spirobifluorenyl, indenyl, pyrenyl, peryl, fluoranthenyl, benzo[9,10]phenanthrenyl; aromatic heterocyclic groups such as pyridyl, thienyl, furanyl, pyrrolyl, quinolyl, isoquinolyl, benzofuranyl, benzothienyl, indolyl, carbazolyl, benzoxazolyl, benzothiazolyl, quinoxalinyl, benzimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothienyl, carbolinyl, etc., and these substituents may be substituted by the substituents exemplified above. In addition, the benzene ring substituted with these substituents, or multiple substituents substituted with the same benzene ring, may be bonded to each other via a single bond, a substituted or unsubstituted methylene group, an oxygen atom, or a sulfur atom to form a ring.
[0054] As the "substituent" in the "substituted or unsubstituted carbazole group" represented by B in the general formula (I), the same as the "substituent" in the "substituted aromatic hydrocarbon group", "substituted aromatic heterocyclic group" or "substituted condensed polycyclic aromatic group" represented by A in the general formula (I) can be listed, and the same forms can be listed.
[0055] The “aromatic hydrocarbon group”, “aromatic heterocyclic group” or “condensed polycyclic aromatic group” represented by R in the general formula (I) may be the same as the “aromatic hydrocarbon group”, “aromatic heterocyclic group” or “condensed polycyclic aromatic group” in the “substituted or unsubstituted aromatic hydrocarbon group”, “substituted or unsubstituted aromatic heterocyclic group” or “substituted or unsubstituted condensed polycyclic aromatic group” represented by A in the general formula (I), and the same forms that may be present may also be mentioned.
[0056] Examples of the “divalent aromatic hydrocarbon group”, “divalent aromatic heterocyclic group” or “divalent condensed polycyclic aromatic group” represented by L1 to L3 in the general formula (I) include groups excluding one hydrogen atom from the “aromatic hydrocarbon group”, “aromatic heterocyclic group” or “condensed polycyclic aromatic group” in the “substituted or unsubstituted aromatic hydrocarbon group”, “substituted or unsubstituted aromatic heterocyclic group” or “substituted or unsubstituted condensed polycyclic aromatic group” represented by A in the general formula (I).
[0057] L2 in the general formula (I) is preferably a biphenylene group, and more preferably a 2,4'-biphenylene group or a 3,4'-biphenylene group.
[0058] L3 in the general formula (I) is preferably a phenylene group, and more preferably a 1,4-phenylene group.
[0059] As R in the general formula (I), a phenyl group or a naphthyl group is more preferable.
[0060] As C in the general formula (I), 1,3-naphthylene, 2,4-naphthylene, 2,5-naphthylene or 2,8-naphthylene is more preferable.
[0061] The aromatic amine compound represented by the above general formula (I) suitable for use in the organic EL component of the present invention is preferably used as a constituent material of the hole injection layer, hole transport layer, electron blocking layer or light-emitting layer of the organic EL component, and is more preferably used as a constituent material of the hole transport layer or electron blocking layer.
[0062] [Effects of the invention]
[0063] Compared with previous hole transport materials, the aromatic amine compounds of the present invention have the following characteristics: (1) good hole injection characteristics, (2) large hole mobility, (3) excellent electron blocking ability, (4) high electron tolerance, (5) stable existence in a thin film state, (6) excellent heat resistance, etc. The aromatic amine compounds of the present invention are used in organic EL components to obtain (7) high luminous efficiency, (8) low luminous starting voltage, (9) low practical driving voltage, (10) long life, etc.
[0064] That is, the aromatic amine compound of the present invention has the following characteristics: excellent electron blocking ability, high electron tolerance, and stable binding of excitons generated in the light-emitting layer even in a thin film state. Therefore, an organic EL device having an electron blocking layer made of the compound as an electron blocking material can increase the probability of recombination between holes and electrons and suppress thermal deactivation, thereby having a higher luminous efficiency, and can reduce the driving voltage and improve the current tolerance, thereby increasing the maximum luminous brightness.
Brief Description of the Figures
[0066] Figure 1 As preferred specific examples of the aromatic amine compound represented by the general formula (I), the following diagrams show compounds (1) to (12).
[0067] Figure 2 The following are diagrams showing compounds (13) to (24) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0068] Figure 3 As preferred specific examples of the aromatic amine compound represented by the general formula (I), the following diagrams show compounds (25) to (36).
[0069] Figure 4 As preferred specific examples of the aromatic amine compound represented by the general formula (I), the following diagrams show compounds (37) to (48).
[0070] Figure 5 The following diagrams show compounds (49) to (60) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0071] Figure 6 The following diagrams show compounds (61) to (72) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0072] Figure 7 The following are diagrams showing compounds (73) to (84) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0073] Figure 8 The following diagrams show compounds (85) to (96) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0074] Fig. 9 The following diagrams show compounds (97) to (108) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0075] Fig.10The following are diagrams showing compounds (109) to (120) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0076] Fig.11 The following diagrams show compounds (121) to (135) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0077] Fig.12 The following diagrams show compounds (136) to (147) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0078] Fig.13 The following diagrams show compounds (148) to (161) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0079] Fig.14 The following diagrams show compounds (162) to (176) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0080] Fig.15 The following diagrams show compounds (177) to (188) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0081] Fig.16 The following diagrams show compounds (189) to (203) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0082] Fig.17 The following diagrams show compounds (204) to (215) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0083] Fig.18 The following diagrams show compounds (216) to (228) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0084] Fig.19 The following are diagrams showing compounds (229) to (239) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0085] Fig. 20 The following are diagrams showing compounds (240) to (242) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0086] Fig.21 The following diagrams show compounds (253) to (261) as preferred specific examples of the aromatic amine compound represented by the general formula (I).
[0087] Fig. 22 It is a figure which shows the structure of the organic EL module of Examples 21-38 and Comparative Examples 1-3.
[0088] [Implementation Method]
[0089] Although the aromatic amine compounds of the present invention are novel compounds, these compounds themselves can be synthesized according to known methods.
[0090] Among the aromatic amine compounds represented by the general formula (I) above that are suitable for use in the organic EL device of the present invention, specific examples of preferred compounds are shown below. Figure 1 to Figure 21 , but are not limited to these compounds.
[0091] The purification of the aromatic amine compound represented by the general formula (I) can be carried out by the following well-known methods: purification using a column chromatography chart, adsorption purification using silica gel, activated carbon, activated clay, etc., recrystallization using a solvent, or crystallization, sublimation purification. The compound can be identified by NMR (Nuclear Magnetic Resonance) analysis. As physical property values, the melting point, glass transition point (Tg) and work function determination can be listed. The melting point is an indicator of vapor deposition, the glass transition point (Tg) is an indicator of the stability of the thin film state, and the work function is an indicator of hole injection, hole transport, or electron blocking properties.
[0092] The melting point and the glass transition point (Tg) can be measured, for example, using a powder with a high-sensitivity differential scanning calorimeter (DSC3100SA manufactured by Bruker AXS).
[0093] The work function can be determined, for example, by forming a 100 nm thin film on an ITO (Indium Tin Oxides) substrate and using an ionization potential measuring apparatus (PYS-202, manufactured by Sumitomo Heavy Industries, Ltd.).
[0094] As the structure of the organic EL component of the present invention, it can be listed as follows: an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode are sequentially included on a substrate; an electron blocking layer is provided between the hole transport layer and the light-emitting layer; and a hole blocking layer is provided between the light-emitting layer and the electron transport layer. In these multilayer structures, one organic layer can serve as several layers at the same time. For example, one organic layer can also be configured as follows: serving as both a hole injection layer and a hole transport layer; serving as both an electron injection layer and an electron transport layer. In addition, it can be configured as a stacking of organic layers having the same function into two or more layers, or it can be configured as follows: stacking the hole transport layer into two layers; stacking the light-emitting layer into two layers; stacking the electron transport layer into two layers.
[0095] As the anode of the organic EL component of the present invention, an electrode material with a large work function such as ITO or gold is used. As the material of the hole injection layer of the organic EL component of the present invention, the following can be used: porphyrin compounds represented by copper phthalocyanine; star-shaped triphenylamine derivatives; aromatic amine compounds having the following structure, that is, having two or more triphenylamine structures or carbazole structures in the molecule, these structures are respectively connected by a single bond or a divalent group not including a heteroatom; acceptor heterocyclic compounds such as hexacyanoazabenzo[9,10]phenanthrene; and coating-type polymer materials. These materials can be formed into thin films by known methods such as evaporation, spin coating and inkjet.
[0096] The arylamine compound of the present invention has excellent hole injection and transport performance, film stability and durability. Thus, the hole transport efficiency of the light-emitting layer of the organic EL component having a hole injection layer and / or a hole transport layer made by using the compound as a hole injection material and / or a hole transport material is improved, the luminous efficiency is improved, and the driving voltage is reduced, thereby improving the durability of the component, thereby obtaining the characteristics of high efficiency, low driving voltage and long life.
[0097] As materials for the hole injection layer and hole transport layer of the organic EL component of the present invention, in addition to the aromatic amine compounds of the present invention, the following can be used: N,N'-diphenyl-N,N'-di(m-tolyl)-benzidine (TPD) or N,N'-diphenyl-N,N'-di(α-naphthyl)-benzidine (NPD), benzidine derivatives such as N,N,N',N'-tetraphenylbenzidine; 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC); and aromatic amine compounds having the following structure, i.e., having two or more triphenylamine structures or carbazole structures in the molecule, each of which is connected by a single bond or a divalent group that does not include a heteroatom. These materials can be formed into a film alone or by mixing multiple materials, and each of them can be used as a single layer. In addition, it can also be set as a laminated structure of layers formed by forming these materials alone, a laminated structure of layers formed by mixing, or a laminated structure of layers formed by forming these materials alone and layers formed by mixing multiple materials. In addition, as the material of the hole injection and transport layer, a coating type polymer material such as poly(3,4-ethylenedioxythiophene) (PEDOT) / poly(styrenesulfonic acid) (PSS) can be used. These materials can be formed into a thin film by a known method such as vapor deposition, spin coating, and inkjet.
[0098] In addition, the hole injection layer or the hole transport layer can use: materials commonly used in these layers are P-doped with tribromophenylamine hexachloroantimony, axialene derivatives (for example, refer to Patent Document 6), etc.; and polymer compounds having the structure of benzidine derivatives such as TPD in their partial structures.
[0099] The aromatic amine compound of the present invention has the following characteristics: excellent electron blocking ability, high electron tolerance, and stable binding of excitons generated in the light-emitting layer in a thin film state. Therefore, an organic EL device having an electron blocking layer made by using the compound as an electron blocking material can increase the probability of recombination of holes and electrons and inhibit thermal deactivation, thereby having a higher luminous efficiency, and can reduce the driving voltage and improve the current tolerance, thereby increasing the maximum luminous brightness.
[0100] As the material of the electron blocking layer of the organic EL component of the present invention, in addition to the aromatic amine compound of the present invention, the following can be used: 4,4',4"-tri(N-carbazolyl)triphenylamine (TCTA), 9,9-bis[4-(carbazol-9-yl)phenyl]fluorene, 1,3-bis(carbazol-9-yl)benzene (mCP), 2,2-bis(4-carbazol-9-yl)phenyl)adamantane (Ad-Cz) and other carbazole derivatives; 9-[4-(carbazol-9-yl)phenyl]-9-[4-(triphenylsilyl)phenyl]-9H-fluorene as the material of the electron blocking layer of the organic EL component of the present invention. Representative compounds having triphenylsilyl and triarylamine structures, such as compounds having electron blocking effects. These materials can also serve as materials for hole transport layers. These materials can be formed into films alone or as a mixture of multiple materials, and can be used as single layers. In addition, it can also be a laminated structure of layers formed by forming these materials alone, a laminated structure of layers formed by mixing them, or a laminated structure of layers formed by forming these materials alone and a laminated structure of layers formed by mixing multiple materials. These materials can be formed into thin films by known methods such as evaporation, spin coating, and inkjet.
[0101] The aromatic amine compound of the present invention has excellent hole transport properties and a wide band gap. Therefore, an organic EL component having a light-emitting layer made of the compound as a main material carries a fluorescent light-emitting body or a phosphorescent light-emitting body or a delayed fluorescent light-emitting body called a dopant to form a light-emitting layer, thereby reducing the driving voltage and improving the luminous efficiency.
[0102] As the material of the light-emitting layer of the organic EL component of the present invention, in addition to the aromatic amine compound of the present invention, metal complexes of quinolinol derivatives including tris(8-quinolinol)aluminum (Alq3), various metal complexes, anthracene derivatives, bis-styrylbenzene derivatives, pyrene derivatives, oxazole derivatives, poly-p-phenylene vinylene derivatives, etc. can be used. In addition, the light-emitting layer can also be composed of a host material and a dopant material. As the host material, an anthracene derivative is preferably used, but in addition to the above-mentioned light-emitting materials including the aromatic amine compound of the present invention, heterocyclic compounds having a partial structure of an indole ring as a condensed ring, heterocyclic compounds having a partial structure of a carbazole ring as a condensed ring, carbazole derivatives, thiazole derivatives, benzimidazole derivatives, and polydialkylfluorene derivatives can be used. In addition, as a dopant material, quinacridone, coumarin, rubrene, perylene and their derivatives, benzopyran derivatives, rhodamine derivatives, and aminostyryl derivatives can be used. These materials can be formed into a film alone, or a plurality of them can be mixed to form a film, and can be used as a single layer respectively. In addition, a laminated structure of layers formed by forming these materials individually, a laminated structure of layers formed by mixing these materials, or a laminated structure of layers formed by forming these materials individually and layers formed by mixing multiple materials may be used. These materials can be formed into a thin film by a known method such as a vapor deposition method, a spin coating method, and an inkjet method.
[0103] In addition, phosphorescent light emitters can also be used as light-emitting materials. As phosphorescent light emitters, phosphorescent light emitters of metal complexes such as iridium or platinum can be used. For example, green phosphorescent light emitters such as Ir(ppy)3, blue phosphorescent light emitters such as FIrpic and FIr6, and red phosphorescent light emitters such as Btp2Ir(acac) can be listed. As the main material at this time, the main materials for hole injection and transport properties include 4,4'-di(N-carbazolyl)biphenyl (CBP), TCTA, mCP and other carbazole derivatives, etc., and the aromatic amine compounds of the present invention can be listed. The main materials for electron transport properties can be listed as para-bis(triphenylsilyl)benzene (UGH2) or 2,2',2"-(1,3,5-phenylene)-tris(1-phenyl-1H-benzimidazole) (TPBI), etc. By using this material, high-performance organic EL components can be made.
[0104] When the host material is doped with a phosphorescent light-emitting material, in order to avoid concentration quenching, it is preferably doped in a range of 1 to 30 weight percent relative to the entire light-emitting layer by co-evaporation.
[0105] In addition, as the light-emitting material, PIC-TRZ (2-biphenyl-4,6-bis(12-phenylindole[2,3-a]carbazol-11-yl)-1,3,5-triazine, 2-biphenyl-4,6-bis(12-phenylindole[2,3-a]carbazol-11-yl)-1,3,5-triazine), CC2TA (2,4-bis{3-(9H-carbazol-9-yl)-9H-carbazol-9-yl}-6-phenyl-1,3,5-triazine) can also be used. Materials that emit delayed fluorescence include CDCB (Carbazolyl Dicyanobenzene, carbazolyl dicyanobenzene) derivatives such as 2,4-bis{3-(9H-carbazol-9-yl)-9H-carbazol-9-yl}-6-phenyl-1,3,5-triazine), PXZ-TRZ (benzoxazine-2,4,6-triphenyl-1,3,5-triazine, benzoxazine-2,4,6-triphenyl-1,3,5-triazine), 4CzIPN (2,4,5,6-Tetrakis(9-carbazol)-4,6-dicyanobenzene, 2,4,5,6-tetrakis(9-carbazolyl)isophthalonitrile) (for example, see Non-Patent Document 3). These materials can be formed into thin films by known methods such as vapor deposition, spin coating, and inkjet.
[0106] As the material of the hole blocking layer of the organic EL component of the present invention, metal complexes of quinolinol derivatives such as vasocuproine (BCP), bis (2-methyl-8-quinolinol) -4- (phenylphenol) aluminum (BAlq), various rare earth complexes, oxazole derivatives, triazole derivatives and triazine derivatives can be used. Compounds with hole blocking effects. These materials can also be used as materials for the electron transport layer. These materials can be formed into a film alone, or they can be mixed into a film of multiple materials, and can be used as a single layer. In addition, it can also be set to a laminated structure of layers obtained by forming these materials individually, a laminated structure of layers formed by mixing, or a laminated structure of layers obtained by forming these materials individually and layers formed by mixing multiple materials. These materials can be formed into thin films by known methods such as evaporation, spin coating and inkjet.
[0107] As the material of the electron transport layer of the organic EL component of the present invention, metal complexes of quinolinol derivatives including Alq3 and BAlq, various metal complexes, triazole derivatives, triazine derivatives, oxadiazole derivatives, pyridine derivatives, pyrimidine derivatives, benzimidazole derivatives, thiadiazole derivatives, anthracene derivatives, carbodiimide derivatives, quinoxaline derivatives, pyridoindole derivatives, phenanthroline derivatives and silylheterocyclopentadiene derivatives can be used. These materials can be formed into films alone or mixed with multiple materials, and can be used as single layers respectively. In addition, it can also be set as a laminated structure of layers obtained by forming films of these materials alone, a laminated structure of layers formed by mixing, or a laminated structure of layers obtained by forming films of these materials alone and layers formed by mixing multiple materials. These materials can be formed into thin films by known methods such as evaporation, spin coating and inkjet.
[0108] As the material of the electron injection layer of the organic EL device of the present invention, alkali metal salts such as lithium fluoride and cesium fluoride, alkaline earth metal salts such as magnesium fluoride, metal complexes of quinolyl derivatives such as lithium quinolate, metal oxides such as aluminum oxide, and metals such as ytterbium (Yb), samarium (Sm), calcium (Ca), strontium (Sr), and cesium (Cs) can be used. The electron injection layer can be omitted by selecting a preferred electron transport layer and cathode.
[0109] In addition, for the electron injection layer and the electron transport layer, metal N such as cesium may be doped into conventional materials of these layers.
[0110] As the cathode of the organic EL device of the present invention, metals with a relatively low work function such as aluminum and alloys with an even lower work function such as magnesium-silver alloy, magnesium-indium alloy and aluminum-magnesium alloy can be used as electrode materials. [Example]
[0111] Hereinafter, the embodiments of the present invention will be described in more detail in Examples. However, the present invention is not limited to the following Examples unless the gist of the invention is exceeded.
[0112] [Example 1]
[0113] <Synthesis of Compound (2)>
[0114] 9.5 g of N-{4-(3-phenylnaphthalen-1-yl)phenyl}-[1,1'-biphenyl]-4-amine, 9.0 g of 9-(4'-chloro-[1,1'-biphenyl]-2-yl)-carbazole, 3.1 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 95 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 6.6 g of compound (2) (yield: 40.6%).
[0115]
[0116] The structure of the obtained white powder was identified using NMR.
[0117] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0118] δ(ppm)=8.07(2H),8.05(1H),7.97(2H),7.77(2H),7.73(1H),7.71(1H),7.62-7.54(5H ),7.50(4H),7.42(5H),7.34(2H),7.31(3H),7.23(2H),7.10(2H),6.92(4H),6.82(4H).
[0119] [Example 2]
[0120] <Synthesis of Compound (21)>
[0121] 10.0 g of N-phenyl-4-(1-phenylnaphthalen-3-yl)aniline, 10.5 g of 9-(4'-chloro-[1,1'-biphenyl]-2-yl)-carbazole, 3.9 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.2 g of tris(dibenzylideneacetone)dipalladium(0) and 100 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred for 3 hours under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (support: silica gel, eluent: dichloromethane / n-heptane) to obtain 14.0 g of compound (21) (yield: 75.5%).
[0122]
[0123] The structure of the obtained white powder was identified using NMR.
[0124] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0125] δ(ppm)=8.06(2H),7.99(1H),7.94(1H),7.89(1H),7.71(1H),7.66(1H),7.63-7.48(10H),7.46(1H ),7.40(1H),7.30(2H),7.23(2H),7.16(2H),7.08(2H),6.96(1H),6.85(2H),6.80(4H),6.68(2H).
[0126] [Example 3]
[0127] <Synthesis of Compound (22)>
[0128] 9.5 g of N-{4-(1-phenylnaphthalen-3-yl)phenyl}-[1,1'-biphenyl]-4-amine, 9.0 g of 9-(4'-chloro-[1,1'-biphenyl]-2-yl)-carbazole, 3.1 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 95 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (support: silica gel, eluent: dichloromethane / n-heptane) to obtain 6.4 g of compound (22) (yield: 39.5%).
[0129]
[0130] The structure of the obtained white powder was identified using NMR.
[0131] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0132] δ(ppm)=8.08(2H),8.01(1H),7.95(1H),7.89(1H),7.72(1H),7.67(1H),7.61(1H),7.60-7.49(1 2H),7.49-7.37(6H),7.31(3H),7.24(1H),7.09(2H),6.90(2H),6.86(2H),6.83(2H),6.74(2H).
[0133] [Example 4]
[0134] <Synthesis of Compound (42)>
[0135] 7.0 g of N-phenyl-4-(1-phenylnaphthalen-3-yl)aniline, 8.0 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 3.6 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 150 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was crystallized and purified using a dichloromethane / acetone mixed solvent to obtain 10.0 g of compound (42) (yield: 77.0%).
[0136]
[0137] The structure of the obtained white powder was identified using NMR.
[0138] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0139] δ(ppm)=8.15(2H),8.03(1H),7.93(1H),7.89(1H),7.79(1H),7.69(1H),7.65 (4H),7.57-7.45(10H),7.45-7.37(4H),7.29(4H),7.25-7.17(6H),7.07(1H).
[0140] [Example 5]
[0141] <Synthesis of Compound (43)>
[0142] 9.0 g of N-{4-(1-phenylnaphthalen-3-yl)phenyl}-[1,1'-biphenyl]-4-amine, 8.5 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 2.9 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 90 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 3.0 g of compound (43) (yield: 19.4%).
[0143]
[0144] The structure of the obtained white powder was identified using NMR.
[0145] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0146] δ(ppm)=8.16(2H),8.05(1H),7.95(1H),7.90(1H),7.80(1H),7.69(5H),7.62-7.47(15H),7.47-7.38(6H),7.36-7.24(8H).
[0147] [Example 6]
[0148] <Synthesis of Compound (60)>
[0149] 9.5 g of N-([1,1'-biphenyl]-4-yl)-4'-(carbazole-9-yl)-[1,1'-biphenyl]-4-amine, 7.4 g of 3-(4-chlorophenyl)-1-phenyl-naphthalene, 3.8 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 170 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was recrystallized and purified using a toluene solvent to obtain 10.9 g of compound (60) (yield: 73.0%).
[0150]
[0151] The structure of the obtained white powder was identified using NMR.
[0152] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0153] δ(ppm)=8.16(2H),8.07(1H),7.96(1H),7.91(1H),7.82(2H),7.73(2H),7.70(1H),7.62(6H),7.56(4H),7.54-7.39(11H),7.31(9H).
[0154] [Example 7]
[0155] <Synthesis of Compound (30)>
[0156] 6.7 g of N-phenyl-4-(3-phenylnaphthalen-1-yl)aniline, 7.0 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 2.6 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 70 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 10.1 g of compound (30) (yield: 81.3%).
[0157]
[0158] The structure of the obtained white powder was identified using NMR.
[0159] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0160] δ(ppm)=8.19(2H),8.08-8.04(2H),7.99(1H),7.83-7.67(6H),7.61(2H),7.57-7.27(22H),7.13(1H).
[0161] [Example 8]
[0162] <Synthesis of Compound (31)>
[0163] 8.0 g of N-{4-(3-phenylnaphthalen-1-yl)phenyl}-[1,1'-biphenyl]-4-amine, 7.0 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 2.6 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 80 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 2.7 g of compound (31) (yield: 19.7%).
[0164]
[0165] The structure of the obtained white powder was identified using NMR.
[0166] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0167] δ(ppm)=8.20(2H),8.08-8.06(2H),8.00(1H),7.85-7.40(26H),7.37-7.32(9H).
[0168] [Example 9]
[0169] <Synthesis of Compound (46)>
[0170] 8.0 g of N-{4-(4-phenylnaphthalen-2-yl)phenyl}-[1,1'-biphenyl]-2-amine, 7.6 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 3.4 g of sodium tert-butoxide, 0.2 g of bis[tri(tert-butylphosphine)]palladium(0) and 160 ml of toluene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 9.9 g of compound (46) (yield: 72.4%).
[0171]
[0172] The structure of the obtained white powder was identified using NMR.
[0173] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0174] δ(ppm)=8.19(2H),8.00(1H),7.95(1H),7.90(1H),7.74(1H),7.67-7.64(3H),7.58-7.31(22H),7.22(2H),7.17-7.11(3H),7.01(4H).
[0175] [Example 10]
[0176] <Synthesis of Compound (85)>
[0177] 10.0 g of 3'-(carbazol-9-yl)-N-phenyl-[1,1'-biphenyl]-4-amine, 8.1 g of 2-(4-chlorophenyl)-6-phenyl-naphthalene, 3.5 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.5 g of tris(dibenzylideneacetone)dipalladium(0) and 100 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, stirred for 30 minutes, and then Cellite filtered at 90°C and the solvent was removed by reduced pressure distillation. The obtained mixture was purified by crystallization using a toluene / acetone mixed solvent to obtain 9.8 g of compound (85) (yield: 58.4%).
[0178]
[0179] The structure of the obtained light yellow powder was identified using NMR.
[0180] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0181] δ(ppm)=8.20(2H),8.08(2H),7.98(2H),7.82(2H),7.79(1H),7.77(2H),7.74-7.66(4H) ,7.59(2H),7.57-7.50(5H),7.46(2H),7.42(1H),7.34(4H),7.28-7.23(6H),7.12(1H).
[0182] [Example 11]
[0183] <Synthesis of Compound (96)>
[0184] 10.0 g of N-{4-(2-phenylnaphthalen-7-yl)phenyl}-[1,1'-biphenyl]-4-amine, 8.7 g of 9-(4'-chloro-[1,1'-biphenyl]-2-yl)-carbazole, 3.2 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.4 g of tris(dibenzylideneacetone)dipalladium(0) and 100 ml of xylene were added to a nitrogen-substituted reaction vessel, and the mixture was stirred overnight under heating and reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, the mixture was filtered through Cellite at 90°C and the solvent was removed by vacuum distillation. The obtained mixture was separated by column chromatography (support: silica gel, eluent: dichloromethane / n-heptane) to obtain 7.9 g of compound (96) (yield: 46.2%).
[0185]
[0186] The structure of the obtained light yellow powder was identified using NMR.
[0187] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0188] δ(ppm)=8.12(2H),8.10(2H),7.95(2H),7.76(5H),7.67-7.50(9H),7.50-7.39(5H), 7.34(3H),7.28(2H),7.13(2H),6.95(1H),6.92(2H),6.89(2H),6.86(1H),6.77(2H).
[0189] [Example 12]
[0190] <Synthesis of Compound (245)>
[0191] 10.0 g of N-phenyl-4-(4-phenylnaphthalen-1-yl)-aniline, 9.5 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 5.2 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.5 g of tris(dibenzylideneacetone)dipalladium(0) and 100 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (support: silica gel, eluent: dichloromethane / n-heptane) to obtain 8.5 g of compound (245) (yield: 45.8%).
[0192]
[0193] The structure of the obtained light yellow powder was identified using NMR.
[0194] use 1 H-NMR (DMSO (dimethyl sulfoxide)) detected the following 36 hydrogen signals.
[0195] δ(ppm)=8.27(2H),8.01(1H),7.89-7.84(3H),7.80-7.74(3H),7.60-7.45(16H),7.41(2H),7.32(2H),7.23-7.14(7H).
[0196] [Example 13]
[0197] <Synthesis of Compound (247)>
[0198] 14.0 g of N-{4-(4-phenylnaphthalen-1-yl)phenyl}-dibenzofuran-3-amine, 11.8 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 3.5 g of sodium tert-butoxide, 0.5 g of tert-butylphosphine (50 wt% toluene solution), 0.6 g of tris(dibenzylideneacetone)dipalladium(0) and 140 ml of xylene were added to a nitrogen-substituted reaction vessel, and the mixture was stirred overnight under heating and reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, the mixture was filtered through Cellite at 90°C and the solvent was removed by reduced pressure distillation. The obtained mixture was purified by crystallization using a toluene / acetone mixed solvent to obtain 13.4 g of compound (247) (yield: 56.7%).
[0199]
[0200] The structure of the obtained light yellow powder was identified using NMR.
[0201] use 1 H-NMR (DMSO) detected the following 38 hydrogen signals.
[0202] δ(ppm)=8.27(2H),8.13-8.08(2H),8.03(1H),7.91-7.76(6H),7.66(1H),7.61-7.38(19H),7.33-7.23(7H).
[0203] [Example 14]
[0204] <Synthesis of Compound (249)>
[0205] 10.0 g of N-phenyl-4-{4-(naphthalene-2-yl)naphthalene-1-yl}-aniline, 9.2 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 3.4 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.4 g of tris(dibenzylideneacetone)dipalladium(0) and 100 ml of xylene were added to a nitrogen-substituted reaction vessel, and the mixture was stirred overnight under heating and reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, the mixture was filtered through Cellite at 90°C and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (support: silica gel, eluent: dichloromethane / n-heptane) to obtain 7.3 g of compound (249) (yield: 41.6%).
[0206]
[0207] The structure of the obtained white powder was identified using NMR.
[0208] use 1 H-NMR (CDCl3) detected the following 38 hydrogen signals.
[0209] δ(ppm)=8.19(2H),8.14(1H),8.05-7.92(5H),7.83(1H),7.71(3H),7.64-7.43(15H),7.40-7.29(10H),7.13(1H).
[0210] [Example 15]
[0211] <Synthesis of Compound (252)>
[0212] 9.0 g of N-phenyl-4-(1-phenylnaphthalen-5-yl)-aniline, 9.0 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 2.8 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.4 g of tris(dibenzylideneacetone)dipalladium(0) and 90 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was purified by recrystallization using a toluene solvent to obtain 7.9 g of compound (252) (yield: 47.3%).
[0213]
[0214] The structure of the obtained white powder was identified using NMR.
[0215] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0216] δ(ppm)=8.20(2H),8.06(1H),7.92(1H),7.84(1H),7.73(1H),7.69(1H),7.62(2H),7.58-7.43(16H),7.40-7.28(10H),7.13(1H).
[0217] [Example 16]
[0218] <Synthesis of Compound (256)>
[0219] 7.5 g of 3'-(carbazol-9-yl)-N-phenyl-[1,1'-biphenyl]-4-amine, 5.9 g of 7-(4-chlorophenyl)-1-phenyl-naphthalene, 3.5 g of tert-butoxysodium, 0.3 g of tert-butylphosphine (50 wt% toluene solution), 0.3 g of tris(dibenzylideneacetone)dipalladium(0) and 75 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, stirred for 30 minutes, and then Cellite filtered at 90°C and the solvent was removed by reduced pressure distillation. The obtained mixture was purified by recrystallization using a toluene solvent to obtain 6.9 g of compound (256) (yield: 58.5%).
[0220]
[0221] The structure of the obtained white powder was identified using NMR.
[0222] use 1 H-NMR (CDCl3) detected the following 36 hydrogen signals.
[0223] δ(ppm)=8.19(2H),8.11(1H),7.99(1H),7.89(1H),7.80-7.76(2H),7.72 -7.65(2H),7.58-7.43(16H),7.35-7.29(4H),7.22-7.18(6H),7.09(1H).
[0224] [Example 17]
[0225] <Synthesis of Compound (258)>
[0226] 7.8 g of N-phenyl-4-(1-phenylnaphthalen-6-yl)-aniline, 8.2 g of 9-(4'-chloro-[1,1'-biphenyl]-3-yl)-carbazole, 3.0 g of sodium tert-butoxide, 0.4 g of tert-butylphosphine (50 wt% toluene solution), 0.4 g of tris(dibenzylideneacetone)dipalladium(0) and 80 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was separated by column chromatography (carrier: silica gel, eluent: dichloromethane / n-heptane) to obtain 11.6 g of compound (258) (yield: 80.2%).
[0227]
[0228] The structure of the obtained white powder was identified using NMR.
[0229] use 1 H-NMR (DMSO) detected the following 36 hydrogen signals.
[0230] δ (ppm) = 8.27 (3H), 8.02 (1H), 7.88-7.74 (9H), 7.63-7.37 (14H), 7.33-7.29 (2H), 7.12-7.19 (7H).
[0231] [Example 18]
[0232] <Synthesis of Compound (261)>
[0233] 7.5 g of N-([1,1'-biphenyl]-4-yl)-2'-(carbazole-9-yl)-[1,1'-biphenyl]-4-amine, 5.0 g of 1-(4-chlorophenyl)-7-phenyl-naphthalene, 3.0 g of sodium tert-butoxide, 0.2 g of tert-butylphosphine (50 wt% toluene solution), 0.3 g of tris(dibenzylideneacetone)dipalladium(0) and 170 ml of xylene were added to a nitrogen-substituted reaction vessel, and stirred overnight under heating reflux. Thereafter, silica gel was added to the reaction solution, and after stirring for 30 minutes, Cellite filtration was performed at 90°C, and the solvent was removed by reduced pressure distillation. The obtained mixture was crystallized and purified using a dichloromethane / acetone mixed solvent to obtain 5.5 g of compound (261) (yield: 46.8%).
[0234]
[0235] The structure of the obtained white powder was identified using NMR.
[0236] use 1 H-NMR (CDCl3) detected the following 40 hydrogen signals.
[0237] δ(ppm)=8.21(1H),8.08(2H),8.01(1H),7.89(1H),7.80-7.75(2H),7.67 -7.31(21H),7.24(2H),7.12(2H),6.95-6.92(4H),6.88(2H),6.81(2H).
[0238] [Example 19]
[0239] The calorimeter was a high-sensitivity differential scanning calorimeter (made by Bruker AXS, DSC). 31 00SA), the melting point and glass transition point of the aromatic amine compound represented by the general formula (I) were measured. The results are shown in Table 1.
[0240]
Table 1
[0241]
[0242]
[0243] The aromatic amine compounds represented by the general formula (I) of Examples 1 to 18 have a glass transition point of 100° C. or higher and are relatively stable in a thin film state.
[0244] [Example 20]
[0245] Using the aromatic amine compounds represented by the general formula (I) of Examples 1 to 18, 100 nm thick vapor-deposited films were prepared on ITO substrates, and the work functions were measured using an ionization potential measuring apparatus (PYS-202 manufactured by Sumitomo Heavy Industries, Ltd.).
[0246]
Table 2
[0247] Work Function Compound 2 5.67eV Compound 21 5.64eV Compound 22 5.62eV Compound 42 5.67eV Compound 43 5.68eV Compound 60 5.68eV Compound 30 5.70eV Compound 31 5.66eV Compound 46 5.68eV Compound 85 5.73eV Compound 96 5.64eV Compound 245 5.68eV Compound 247 5.68eV Compound 249 5.69eV Compound 252 5.69eV Compound 256 5.69eV Compound 258 5.66eV Compound 261 5.65eV
[0248] It is found that the aromatic amine compounds represented by the general formula (I) of Examples 1 to 18 exhibit an appropriate energy level compared to the work function of 5.4 eV of common hole transport materials such as NPD and TPD, and have good hole transport capabilities.
[0249] Therefore, the aromatic amine compound of the present invention can be effectively used as a material for a hole injection layer, a hole transport layer, an electron blocking layer or a light emitting layer of an organic EL device, and can improve the luminous efficiency, driving voltage and durability of the conventional organic EL device.
[0250] [Example 21]
[0251] The organic EL component is manufactured as follows: Fig. 22 As shown, after a reflective ITO electrode serving as a transparent anode 2 is pre-formed on a glass substrate 1, a hole injection layer 3, a hole transport layer 4, an electron blocking layer 5, a light-emitting layer 6, an electron transport layer 7, an electron injection layer 8, a cathode 9, and a covering layer 10 are sequentially vapor-deposited thereon.
[0252] Specifically, a glass substrate 1 formed by sequentially forming a film of ITO with a thickness of 50 nm, a film of a silver alloy with a thickness of 100 nm, and an ITO with a thickness of 5 nm was ultrasonically cleaned for 20 minutes in isopropyl alcohol, and then dried on a hot plate heated to 250° C. for 10 minutes. Thereafter, after a UV (Ultraviolet) ozone treatment for 2 minutes, the glass substrate having the ITO was placed in a vacuum deposition machine and the pressure was reduced to less than 0.001 Pa. Subsequently, an electron acceptor of the following structural formula and a compound (HTM-1) of the following structural formula were binary deposited at a deposition rate ratio of acceptor (Acceptor)-1:compound (HTM (Hole Transport Material)-1) = 3:97, thereby forming a hole injection layer 3 in a film thickness of 10 nm to cover the transparent anode 2. On the hole injection layer 3, a compound (HTM-1) of the following structural formula was formed to a film thickness of 140 nm as a hole transport layer 4. On the hole transport layer 4, the compound (2) of Example 1 was formed to a film thickness of 5 nm as an electron blocking layer 5. The compound (EMD-1) of the following structural formula and the compound (EMH-1) of the following structural formula were binary deposited at a deposition rate ratio of EMD (N,N-bis(5-ethyl-2-hydroxybenzyl)methylamine, N,N-bis(5-ethyl-2-hydroxybenzyl)methylamine)-1:EMH (5-Ethyl-5-methylhydantoin, 5-ethyl-5-methylhydantoin)-1=5:95, thereby forming a light-emitting layer 6 on the electron blocking layer 5 to a film thickness of 20 nm. The compound of the following structural formula (ETM-1) and the compound of the following structural formula (ETM-2) were binary deposited at a deposition rate ratio of ETM (Electron Transport Material)-1:ETM-2=50:50, thereby forming an electron transport layer 7 on the light-emitting layer 6 in a film thickness of 30 nm. On the electron transport layer 7, lithium fluoride was formed as an electron injection layer 8 in a film thickness of 1 nm. On the electron injection layer 8, a magnesium-silver alloy was formed as a cathode 9 in a film thickness of 12 nm. Finally, a compound of the following structural formula (CPL (Caprolactam)-1) was formed as a covering layer 10 in a film thickness of 60 nm. The characteristics of the manufactured organic EL component were measured at room temperature in the atmosphere. The measurement results of the luminescent characteristics when a DC voltage was applied to the manufactured organic EL component are summarized in Table 3.
[0253]
[0254] [Example 22]
[0255] In Example 21, an organic EL device was prepared under the same conditions except that the compound (21) of Example 2 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0256] [Example 23]
[0257] In Example 21, an organic EL device was prepared under the same conditions except that the compound (22) of Example 3 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0258] [Example 24]
[0259] In Example 21, an organic EL device was prepared under the same conditions except that the compound (42) of Example 4 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0260] [Example 25]
[0261] In Example 21, an organic EL device was prepared under the same conditions except that the compound (43) of Example 5 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0262] [Example 26]
[0263] In Example 21, an organic EL device was prepared under the same conditions except that the compound (60) of Example 6 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0264] [Example 27]
[0265] In Example 21, an organic EL device was prepared under the same conditions except that the compound (30) of Example 7 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0266] [Example 28]
[0267] In Example 21, an organic EL device was prepared under the same conditions except that the compound (31) of Example 8 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0268] [Example 29]
[0269] In Example 21, an organic EL device was prepared under the same conditions except that the compound (46) of Example 9 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0270] [Example 30]
[0271] In Example 21, an organic EL device was prepared under the same conditions except that the compound (85) of Example 10 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0272] [Example 31]
[0273] In Example 21, an organic EL device was prepared under the same conditions except that the compound (96) of Example 11 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0274] [Example 32]
[0275] In Example 21, an organic EL device was prepared under the same conditions except that the compound (245) of Example 12 was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0276] [Example 33]
[0277] In Example 21, an organic EL device was prepared under the same conditions except that the compound (247) of Example 13 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0278] [Example 34]
[0279] In Example 21, an organic EL device was prepared under the same conditions except that the compound (249) of Example 14 was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0280] [Example 35]
[0281] In Example 21, an organic EL device was prepared under the same conditions except that the compound (252) of Example 15 was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0282] [Example 36]
[0283] In Example 21, an organic EL device was prepared under the same conditions except that the compound (256) of Example 16 was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0284] [Example 37]
[0285] In Example 21, an organic EL device was prepared under the same conditions except that the compound (258) of Example 17 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0286] [Example 38]
[0287] In Example 21, an organic EL device was prepared under the same conditions except that the compound (261) of Example 18 was used instead of the compound (2) of Example 1 as the material of the electron blocking layer 5. The characteristics of the prepared organic EL device were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL device are summarized in Table 3.
[0288] [Comparative Example 1]
[0289] For comparison, in Example 21, an organic EL component was prepared under the same conditions except that the compound (HTM-2) of the following structural formula was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1 (see Patent Document 7). The characteristics of the prepared organic EL component were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL component are summarized in Table 3.
[0290]
[0291] [Comparative Example 2]
[0292] For comparison, in Example 21, an organic EL component was prepared under the same conditions except that the compound (HTM-3) of the following structural formula was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1 (see Patent Document 8). The characteristics of the prepared organic EL component were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL component are summarized in Table 3.
[0293]
[0294] [Comparative Example 3]
[0295] For comparison, in Example 21, an organic EL component was prepared under the same conditions except that the compound (HTM-4) of the following structural formula was used as the material of the electron blocking layer 5 instead of the compound (2) of Example 1 (see Patent Document 9). The characteristics of the prepared organic EL component were measured at room temperature in the atmosphere. The results of the measurement of the luminescent characteristics when a DC voltage was applied to the prepared organic EL component are summarized in Table 3.
[0296]
[0297] The results of measuring the device life using the organic EL devices prepared in Examples 21 to 38 and Comparative Examples 1 to 3 are summarized in Table 3. The device life was measured when the luminance at the start of luminescence (initial luminance) was set to 2000 cd / m 2 When the static current is driven, the luminance decays to 1900cd / m 2 (When the initial brightness is set to 100%, it is equivalent to 95%: 95% attenuation)
[0298]
Table 3
[0299]
[0300]
[0301] As shown in Table 3, the flow current density is 10 mA / cm 2 The luminous efficiency at a current of is as follows: relative to 8.84 to 9.11 cd / A of the organic EL components of Comparative Examples 1 to 3, the organic EL components of Examples 21 to 38 are 9.82 to 10.42 cd / A, reflecting high efficiency. In addition, the power efficiency is as follows: relative to 8.45 to 8.68 lm / W of the organic EL components of Comparative Examples 1 to 3, the organic EL components of Examples 21 to 38 are 9.39 to 10.08 lm / W, reflecting high efficiency. In addition, it can be seen that the component life (95% attenuation) is as follows: relative to 247 to 328 hours of the organic EL components of Comparative Examples 1 to 3, the organic EL components of Examples 21 to 38 are 422 to 714 hours, reflecting a long life.
[0302] According to the above results, compared with the aromatic amine compounds previously used as hole transport materials, the aromatic amine compounds with a specific structure represented by the general formula (I) of the present invention have a larger hole mobility and excellent electron blocking ability. Therefore, compared with the previous organic EL components, the organic EL components used together with the blue light-emitting layer of the present invention have a higher luminous efficiency and can realize a long-life organic EL component.
[0303]
Industrial Applicability
[0304] The organic EL component using the aromatic amine compound having a specific structure of the present invention can improve the luminous efficiency and the durability of the organic EL component, and thus can be developed for use in, for example, home telephone products or lighting. In addition, the aromatic amine compound of the present invention can be used not only in organic EL components, but also in the field of electronic devices such as electronic photographic photoreceptors, image sensors, photoelectric conversion components, and solar cells.
[0305]
Explanation of symbols
[0306] 1: Glass substrate
[0307] 2: Transparent anode
[0308] 3: Hole injection layer
[0309] 4: Hole transport layer
[0310] 5: Electron blocking layer
[0311] 6: Luminous layer
[0312] 7: Electron transport layer
[0313] 8: Electron injection layer
[0314] 9: Cathode
[0315] 10: Overlay
Claims
1. An aromatic amine compound represented by the following general formula (I): In the formula, A represents a substituted or unsubstituted aromatic hydrocarbon group, a substituted or unsubstituted aromatic heterocyclic group, or a substituted or unsubstituted condensed polycyclic aromatic group, B represents a substituted or unsubstituted carbazolyl group, C represents an unsubstituted naphthylene group, R represents an unsubstituted aromatic hydrocarbon group, an unsubstituted aromatic heterocyclic group, or an unsubstituted condensed polycyclic aromatic group, L1 to L3 represent a single bond, an unsubstituted divalent aromatic hydrocarbon group, an unsubstituted divalent aromatic heterocyclic group, or an unsubstituted divalent condensed polycyclic aromatic group.
2. The aromatic amine compound according to claim 1, wherein C in the general formula (I) is represented by an unsubstituted 1,2-naphthylene, an unsubstituted 1,3-naphthylene, an unsubstituted 2,4-naphthylene, an unsubstituted 2,5-naphthylene, an unsubstituted 2,6-naphthylene, an unsubstituted 2,8-naphthylene or an unsubstituted 2,7-naphthylene. 3 . The aromatic amine compound according to claim 2 , wherein L2 and L3 in the general formula (I) represent unsubstituted phenylene or unsubstituted biphenylene.
4. The aromatic amine compound according to claim 3, wherein R in the general formula (I) represents an unsubstituted phenyl group, an unsubstituted naphthyl group, an unsubstituted dibenzofuranyl group, an unsubstituted phenanthrenyl group, or an unsubstituted biphenyl group. 5 . The aromatic amine compound according to claim 4 , wherein B in the general formula (I) represents a substituted or unsubstituted 9-carbazolyl group, a substituted or unsubstituted 2-carbazolyl group, or a substituted or unsubstituted 3-carbazolyl group. 6 . The aromatic amine compound according to claim 5 , wherein B in the general formula (I) represents an unsubstituted 9-carbazolyl group.
7. An organic electroluminescent (EL) component comprising a pair of electrodes and at least one organic layer sandwiched therebetween, wherein the organic layer comprises the aromatic amine compound according to claim 1 or 2. 8 . The organic EL device according to claim 7 , wherein the organic layer is a hole transport layer. 9 . The organic EL device according to claim 7 , wherein the organic layer is an electron blocking layer.
10. The organic EL device according to claim 7, wherein the organic layer is a hole injection layer.
11. The organic EL device according to claim 7, wherein the organic layer is a light-emitting layer. 12 . An electronic device comprising a pair of electrodes and at least one organic layer sandwiched therebetween, wherein the organic layer comprises the aromatic amine compound according to claim 1 or 2.
Citation Information
Patent Citations
Diarylamino matrix material doped with a mesomeric radialene compound
EP2684932A1
Organic electroluminescent element, and display unit
JP2009076817A
Tetraaryl benzidines
US5639914A
Organic EL element
US5792557A
P-terphenyl compound and photosensitive body for electrophotography using such compound
US7759030B2